2016
DOI: 10.14740/jocmr2377w
|View full text |Cite
|
Sign up to set email alerts
|

LeptospiraExposure and Gardeners: A Case-Control Seroprevalence Study

Abstract: BackgroundLeptospira can be found in soil. However, it is unclear whether occupational exposure to soil may represent a risk for Leptospira infection in humans. Therefore, we sought to determine the association of Leptospira IgG seroprevalence with the occupation of gardener, and to determine the epidemiological characteristics of gardeners associated with Leptospira exposure.MethodsWe performed a case-control study in 168 gardeners and 168 age- and gender-matched control subjects without gardening occupation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
3
1
1
Order By: Relevance
“…In a study in rural Durango, 15.6% seroprevalence of Leptospira infection was found. 9 The seroprevalence of Leptospira infection found in the present study was higher than those reported in several population groups in Mexico including patients with liver diseases (22.7%), 12 meat workers (17.7%), 13 gardeners (6%) 14 and waste pickers (4.4%). 15 However, the seroprevalence found in the current study was lower than the 61% seroprevalence found in dog owners in the east central Mexican state of Veracruz (61%) 16 and veterinarians in Mexico (38.8%).…”
Section: Discussioncontrasting
confidence: 73%
“…In a study in rural Durango, 15.6% seroprevalence of Leptospira infection was found. 9 The seroprevalence of Leptospira infection found in the present study was higher than those reported in several population groups in Mexico including patients with liver diseases (22.7%), 12 meat workers (17.7%), 13 gardeners (6%) 14 and waste pickers (4.4%). 15 However, the seroprevalence found in the current study was lower than the 61% seroprevalence found in dog owners in the east central Mexican state of Veracruz (61%) 16 and veterinarians in Mexico (38.8%).…”
Section: Discussioncontrasting
confidence: 73%
“…In only one of the cases, contact with rodents was reported [22]. Gardening, although it may not have a high association with leptospirosis, in some cases can be the only background, as was reported in one case [14,37]. The remaining two cases, working as a farmer and living in a farmers' village were the only antecedents that helped to reach the diagnosis of leptospirosis; performing different farming activities have already been reported to be significant risk factors for leptospirosis [18,22,38,39].…”
Section: N Discussionmentioning
confidence: 83%
“…Enfermedades de origen común Enfermedades asociadas a la labor del reciclador Brasil (23,34) Bronquitis Hepatitis A México (56)(57)(58) -…”
Section: Paísunclassified